A new species of Hystrichopsylla Taschenberg (Siphonaptera: Hystrichopsyllidae) from the Mexican transition zone - Acosta, Roxana; Morrone, Juan J. (Zootaxa, 2005)
A new flea species, Hystrichopsylla cryptotis, is described from the Sierra Madre Oriental and Sierra Madre del Sur, Mexico. The host of this new species is the shrew Cryptotis mexicana (Coues, 1877) (Mammalia: Soricidae). This flea species is easily recognized by its large size, seven genal combs, and the slender sternum IX, with 13 pairs of thick spiniform setae of different sizes. A key to the Mexican and Guatemalan species of Hystrichopsylla is given. The cladistic analysis indicates that Mexican species of Hystrichopsylla may be arranged in two different species groups: the H. orophila species group (H. orophila Barrera 1952 and H. cryptotis) and the H. dippiei species group (H. dippiei Rotshchild 1902, H. llorentei Ayala and Morales 1990, and H. kris Traub and Johnson 1952). The resolved area cladogram based on their phylogenetic relationships indicates the following relationships: (Sierra Madre Oriental, (Sierra Madre del Sur, Transmexican Volcanic Belt)).